2013
DOI: 10.1371/journal.pone.0080076
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Cycloxygenase and Ornithine Decarboxylase by Diclofenac and Alpha-Difluoromethylornithine Blocks Cutaneous SCCs by Targeting Akt-ERK Axis

Abstract: Non-melanoma skin cancer (NMSC) is the most common type of skin cancer in Caucasian populations. Its increasing incidence has been a major public health concern. Elevated expressions of ODC and COX-2 are associated with both murine and human NMSCs. Inhibition of these molecular targets singly employing their respective small molecule inhibitors showed limited success. Here, we show that combined blockade of ODC and COX-2 using their potent inhibitors, DFMO and diclofenac respectively abrogates growth of A431 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Histology, immunohistochemical or immunofluorescence staining of skin and tumor sections were performed according to the standard protocol as described earlier [22]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histology, immunohistochemical or immunofluorescence staining of skin and tumor sections were performed according to the standard protocol as described earlier [22]. …”
Section: Methodsmentioning
confidence: 99%
“…For Western blot analysis, proteins (60–80 μg) were resolved on 4%, 10% and 15% Tris-glycine gel based on their molecular weights and transferred onto a nitrocellulose membrane (Bio-Rad) as described previously [22]. For sequential antibody reprobing, blots were stripped using Restore western blot stripping buffer (Pierce Biotechnology, Rockford, IL, USA) according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that increased COX‐2 plays important roles in the pathogenesis of both BCC and SCCs , while COX‐2‐mediated production of PGE 2 plays key roles in tumor progression and metastasis via binding to its receptors EP1‐4, these responses are distinct in BCCs vs SCCs . In addition, we and others have shown that tumor proliferation and reduction in apoptosis by UVB‐induced COX‐2 involve activation of a number of signaling pathways including Akt . Thus, administration of both specific and nonspecific inhibitors of COX‐2 provides benefit in intercepting tumor growth .…”
Section: Discussionmentioning
confidence: 95%
“…Our laboratory has focused on identifying on various pharmacological targets for the intervention of UVB-induced NMSCs in various murine models. Accordingly, effects of inhibition of pathways such as cyclooxygenase (COX), ornithine decarboxylase, p53, sonic hedgehog, estrogen receptor and Wnt have been described earlier (5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…These data support the use of DFMO as a chemopreventive agent for NMSC and underscore the relevance of the polyamine pathway in skin tumor development. Evidence from animal models using DFMO in combination with polyamine transport inhibitors 172 , 173 or cyclooxygenase (COX) inhibitors 174 , 175 demonstrated increased efficacy in both chemoprevention and therapy of NMSC. In related clinical trials, the combination of DFMO and the COX inhibitor sulindac was both safe and remarkably effective in preventing recurrence of colorectal adenomas in resected adenoma patients followed-up for 3 years, 176 suggesting this would also be a promising combination in individuals at high risk for NMSC such as organ transplant recipients or Xeroderma pigmentosum (XP) patients.…”
Section: Prospects For Polyamine-based Therapy In Nmscmentioning
confidence: 99%